2019
DOI: 10.4236/jbise.2019.123015
|View full text |Cite
|
Sign up to set email alerts
|

Automated Exudates Detection in Retinal Fundus Image Using Morphological Operator and Entropy Maximization Thresholding

Abstract: Blindness which is considered as degrading disabling disease is the final stage that occurs when a certain threshold of visual acuity is overlapped. It happens with vision deficiencies that are pathologic states due to many ocular diseases. Among them, diabetic retinopathy is nowadays a chronic disease that attacks most of diabetic patients. Early detection through automatic screening programs reduces considerably expansion of the disease. Exudates are one of the earliest signs. This paper presents an automate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Here, the assessment criteria to identify HE presented at pixel level and image level. InKom et al(2019), OD of the fundus image is identified using brightness and variance features using Circular Hough Transformation and masked then the bright patches are segmented based on thresholding and morphological reconstruction techniques. For classification, color, size, and texture features are taken from segmented candidate regions and are categorised with the use of multilayered perceptron neural network (MLP).…”
mentioning
confidence: 99%
“…Here, the assessment criteria to identify HE presented at pixel level and image level. InKom et al(2019), OD of the fundus image is identified using brightness and variance features using Circular Hough Transformation and masked then the bright patches are segmented based on thresholding and morphological reconstruction techniques. For classification, color, size, and texture features are taken from segmented candidate regions and are categorised with the use of multilayered perceptron neural network (MLP).…”
mentioning
confidence: 99%